Review-Recent Advances in Sensor Arrays for the Simultaneous Electrochemical Detection of Multiple Analytes - Ozer, Tugba; Henry, Charles S. (ELECTROCHEMICAL SOC INC, 2021)
In this review, electrochemical sensor arrays were investigated for various chemical/biological sensing applications including proteins, whole cell pathogens, and small molecules. Utilization of multi-electrode arrays is important for monitoring cancer and other diseases by allowing for detection of multiple proteins in a single assay. Various voltammetric, amperometric, and potentiometric techniques have been used for investigating the electrochemical properties of the electrode surfaces. Electrodes modified with different nanomaterials, antibodies, enzymes, aptamers, etc. have been used to improve performance. This review focuses on recent publications that provide insight into the development of sensor arrays based on microfluidic and paper-based devices. We also discuss incorporation of these devices with portable potentiostats and wireless data acquisition technology for simultaneous analysis of multiple targets.
Keywords: THERMOPLASTIC ELECTRODES; FOOD SAFETY; BIOSENSORS; PLATFORM; CHEMOMETRICS; BIOMARKERS; DIAGNOSIS; RESIDUES; BACTERIA; SAMPLES; Electrochemistry; Materials Science